Nurses’ Perception About Spirituality and Providing Spiritual Care in Nursing (Journal of Universal Excellence, 2026)
Research Question (RQ): How do nurses perceive spirituality and their ability to provide spiritual care in nursing? Are there statistically significant differences between nurses' demographic characteristics and their perceptions of spirituality and spiritual care? How can nursing organisations improve nurses' perceptions and delivery of spiritual care?Purpose: The purpose of this study is to highlight the importance of spirituality and spiritual care in nursing staff with the aim of examining nurses' perceptions of spirituality and the provision of spiritual care in nursing.Method: A quantitative descriptive non-experimental method using a survey technique was used.Results: Respondents consider patients' spiritual needs important to their health and well-being. However, nurses face several obstacles in meeting these needs. Formal training of nurses does not provide them with the skills to provide spiritual care. This underscores the need for greater emphasis on spirituality and spiritual care in nursing education to remove barriers to competent care.Organization: Recognising the importance of spirituality in patient care can encourage health care organisations to develop policies and programmes that integrate spiritual care into clinical practise. Integrating spiritual care into nursing practise leads to better patient outcomes and higher quality of nursing care and increases nurses' job satisfaction and fulfilment. It also promotes a more holistic and patient-centred approach and a positive reputation for healthcare organisations.Society: Focusing on the spiritual needs of patients can emphasise social responsibility and promote individual and community awareness of their impact on the environment. Recognising and respecting the spiritual beliefs of people from different cultural backgrounds promotes diversity and inclusion and contributes to an accepting and understanding society. We suggest providing additional training on spirituality for health professionals, which would have a positive impact on more appropriate integration of patients from other cultures into health care.Originality: We did not find much research on spirituality in nursing in the Slovenian literature. Limitations/Future Research: The weaknesses of our survey are related to the low internal consistency of the subcategories and the small sample size. Further psychometric validation of the scale on a larger sample would be needed.
Keywords: religiosity; holistic approach; religious beliefs; cultural sensitivity; spiritual needs